Detection of aflatoxin residues in chicken liver in lima markets - Arbaiza F., Teresa (2009)
Aflatoxins cause a variety of disorders in poultry, especially affecting the liver (aflatoxicosis). Contaminated livers may become a health risk to consumers when expended in food markets. The purpose of the present study was to detect the presence of aflatoxins in chicken livers in Lima food markets. Samples were collected in 16 markets located in various socioeconomic sectors of Lima. From every market livers were subclassified as normal and apparently suspicious. Analysis of 32 samples was conducted at the Laboratory of Biochemistry, Nutrition and Animal Feeding, Veterinary Medicine Faculty, San Marcos University. Aflatoxins were determined through the ELISA method approved by the AOAC Research Institute, using the Veratox HS (high sensitivity, 0, 1, 2, 4, and 8 ppb). Liver samples are quite complex so immunoaffinity extraction columns (NEOCOLUMN for aflatoxins, 04/08) were used. The detection limit was 0.5 ppb. None of the sampled was detected with aflatoxins. The aspect of livers considered as suspicious might be due to other metabolic processes than aflatoxin contamination, but also to the good performance of micotoxin adsorbents in food.